One voice, many voices - Jane Beethoven; Rosanne Emery; Synía Carroll-McQuillan.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1995)
Viewers are introduced to some simple ways of creating harmony : Discover ostinatos, partner songs, rounds, and countermelodies : Discover harmony in different styles of vocal music : See an unusual chorus sing a song with many countermelodies.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - Episode 1: The Story - - Episode 2: Last Old Train's A-Leavin' - - Episode 3: A Ram Sam Sam (Morocco) - - Episode 4: Sandyland and Skip to My Lou - - Episode 5: Row, Row, Row Your Boat - - Episode 6: Great Gettin' Up Morning - - Episode 7: Ballo (Italy) - - Episode 8: Our Melody - -Correlations with The Music Connection - - About the Artists.
Series producers : Jane Beethoven, Rosanne Emery.
Host: Synia Carroll-McQuillan ; Arpeggio
Keywords: Harmony